2016
DOI: 10.12809/hkmj164853
|View full text |Cite
|
Sign up to set email alerts
|

Seatbelt use by pregnant women: a survey of knowledge and practice in Hong Kong

Abstract: Introduction:The use of motor vehicles is common during pregnancy. Correct seatbelt use during pregnancy has been shown to protect both the pregnant woman and her fetus. This survey aimed to evaluate the practices, beliefs, and knowledge of Hong Kong pregnant women of correct seatbelt use, and identify factors leading to reduced compliance and inadequate knowledge.Methods: A self-administered survey was completed by postpartum women in the postnatal ward at the United Christian Hospital, Hong Kong, from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…13 Episiotomy in Asian countries is often justified as "it is thought that the perineum is smaller and tighter in Asians and that routine episiotomy may decrease the risk of perineal tear during delivery". 8 Our episiotomy rates were broadly consistent with those of other low-and middle-income countries.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…13 Episiotomy in Asian countries is often justified as "it is thought that the perineum is smaller and tighter in Asians and that routine episiotomy may decrease the risk of perineal tear during delivery". 8 Our episiotomy rates were broadly consistent with those of other low-and middle-income countries.…”
Section: Discussionsupporting
confidence: 85%
“…In low‐ and middle‐income countries, the overall rates of birth‐related perineal trauma were 46% (95% CI 36%–55%), 24% (95% CI 17%–32%), and 1.4% (95% CI 1.2%–1.7%) for episiotomies, second‐degree tears, and obstetrical anal sphincter injury, respectively, and were relatively high for episiotomy compared with high‐income settings 13 . Episiotomy in Asian countries is often justified as “it is thought that the perineum is smaller and tighter in Asians and that routine episiotomy may decrease the risk of perineal tear during delivery” 8 . Our episiotomy rates were broadly consistent with those of other low‐ and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have found that pregnant women are significantly more likely to use seat belts if they have acquired knowledge on how to wear them correctly during pregnancy. 14,15 In 2007, Japan passed the Road Traffic Act, which, beginning in 2008, required people in both the front and back seats of a car to wear seat belts. 16 Previous studies have found such legislation to be effective: people are more likely to use rear seatbelts if there are laws enforcing the practice.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the current study did not evaluate whether the pregnant women had driving licenses. A similar study conducted in Hong Kong reveals that pregnant women with primary or secondary education had low knowledge about the use of seat belts when compared with women with tertiary education, and hence could not identify the information needs regarding their safety when travelling with their cars or public transport (Lam, To, and Ma 2016). The low desire for knowledge on seat belt usage shows the necessity for nurses to educate pregnant women on the importance of wearing seat belts when in motor vehicles.…”
mentioning
confidence: 97%